Efavirenz concentrations and probability of HIV replication in children - Nontiya Homkham (2018)
Copyright © 2015 Wolters Kluwer Health, Inc. All rights reserved. In 188 HIV-infected children receiving efavirenz, a lower middose (C12) was associated with a higher risk of HIV-1 viral load > 400 copies/ mL (P = 0.03). Simulations for a normalized population receiving US Food and Drug Administration weight-band dosing predicted that 15% of children would have a C12 below target threshold ( < 1.0 mg/L) with a 23% risk of viral replication.